PENGARUH KONSENTRASI INDUSTRI TERHADAP EFISIENSI INDUSTRI KECAP DI INDONESIA (ISIC 15493) - Hasbullah Firmansyah; Bernadette Robiani; Mukhlis Mukhlis (Department of Development Economics, Universitas Sriwijaya, 2015)
This study was aimed at finding the development and influence oh industry concentration on the efficiency of the soy sauce industry in Indonesia. The data were secondary ones taken from 1993 – 2011. This study was based on the theory of industrial organization, industrial concentration, and industrial efficiency. Descriptive quantitative was the method in this study. The degree of the industrial efficiency in soy sauce industry was influenced by the number of companies operating and producing soy sauce. The degree of industrial concentration in soy sauce industry was measured by using value added in industrial concentration divided by the number of soy sauce companies. The degree of soy sauce industrial concentration in the last year of observation was 7296550.747. The degree of industrial efficiency in the last year of observation was 0.91. There was a positive influence of the industrial concentration on the industrial efficiency. It was found that 50 % of the efficiency variable was influenced by the degree of industrial concentration. The rest was influenced by other factors. Keywords: Concentration, efficiency, soy sauce industry, value added